Talk to Me Tenderly : Tell Me Lies - Davis, John Gordon (London Fontana, 1992)
On an isolated farm in the middle of the Australian outback, Helen Mckenzie is alone. While her husband Clyde is thousands of miles away working in a mine to earn the money to keep their teenage children at boarding school, Helen meets Ben and the two strike up a friendship.
Keywords: Queensland -- Australia